The Effects of 8-Week Hydrogen-Rich Water Consumption on Appetite, Body Composition, Sleep Quality, and Circulating Glucagon-like Peptide-1 in Obese Men and Women (HYDRAPPET): A Randomized Controlled Trial - Nikola Todorovic; Sonja Baltic; David Nedeljkovic; Jovan Kuzmanovic; Darinka Korovljev; Dejan Javorac; Katarina Bijelic; Nebojsa Kladar; Alex Tarnava; Sergej M. Ostojic (Medicina, 2025)
Background and Objectives: Preliminary studies indicate that dihydrogen (H2) may affect molecular pathways involved in appetite regulation; however, its role in influencing patient-reported appetite outcomes in individuals with obesity remains uncertain. This randomized, placebo-controlled, double-blind trial aimed to evaluate the effects of H2 supplementation on appetite, body composition, sleep quality, obesity-specific quality of life, and related biomarkers in obese men and women. Materials and Methods: The study included 36 participants (24 females; age 42.1 ± 13.2 years; BMI 30.8 ± 4.2 kg/m2) randomized to receive either 1.0 L of hydrogen-rich water (15 mg of H2) or 1.0 L of control water (0 mg of H2) daily for eight weeks. Results: The results demonstrated that hydrogen-rich water significantly mitigated cravings (p = 0.05), improved subjective sleep quality (p = 0.05), reduced total cholesterol (p = 0.02) and LDL cholesterol (p = 0.04), and increased plasma glucagon-like peptide-1 levels (p = 0.05) compared to the control. No severe adverse effects were reported throughout the trial. Conclusions: These findings suggest that hydrogen-rich water may serve as a safe and effective dietary strategy to address appetite regulation and related metabolic indices in individuals with obesity. The study is registered at ClinicalTrials.gov (NCT06722326).